Immunomodulation Induced During Interferon-α Therapy Impairs the Anti-HBV Immune Response Through CD24+CD38hi B Cells - Fu, Binqing; Wang, Dongyao; Shen, Xiaokun; Guo, Chuang; Liu, Yanyan; Ye, Ying; Sun, Rui; Li, Jiabin; Tian, Zhigang; Wei, Haiming (Frontiers in Immunology, 2020)
Type I interferon is widely used for antiviral therapy, yet has yielded disappointing results toward chronic HBV infection. Here we identify that PEG-IFNα-2b therapy toward persistent infection in humans is a double-edged sword of both immunostimulation and immunomodulation. Our studies of this randomised trial showed persistent PEG-IFNα-2b therapy induced large number of CD24+CD38hi B cells and launched a CD24+CD38hi B cells centered immunosuppressive response, including downregulating functions of T cells and NK cells. Patients with low induced CD24+CD38hi B cells have achieved an improved therapeutic effect. Specifically, using the anti-CD24 antibody to deplete CD24+CD38hi B cells without harming other B cell subsets suggest a promising strategy to improve the therapeutic effects. Our findings show that PEG-IFNα-2b therapy toward persistent infection constitutes an immunomodulation effect, and strategies to identifying the molecular basis for the antiviral versus immunomodulatory effects of PEG-IFNα-2b to selectively manipulate these opposing activities provide an opportunity to ameliorate anti-virus immunity and control viral infection.